2008
DOI: 10.1007/s11738-007-0130-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of a multipurpose leguminous tree (Pterocarpus marsupium Roxb.) using nodal explants

Abstract: Pterocarpus marsupium (Bijasal) is a valuable multipurpose forest tree. The regeneration rate in natural habitat is low and the tree is overexploited. An in vitro propagation protocol has been developed from nodal explants obtained from in vitro raised 18-day-old axenic seedlings. The highest shoot regeneration frequency (85%), maximum number of multiple shoots (8.6) as well as length (4.8 cm) were induced from nodal explants on Murashige and Skoog (MS) medium amended with 4.0 lM 6-benzyladenine (BA), 0.5 lM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 26 publications
6
38
0
1
Order By: Relevance
“…The shoot proliferation rate was significantly affected by addition of Gln, ADS and CH. The simulative role of ADS in shoot multiplication has been emphasized from time to time in various plants (Husain and Anis, 2004;Dhar and Upreti, 1999;Husain et al, 2008). In our study, we found 50 mg/L of ADS as highly effective for enhancing the shoot multiplication rate (4.88 shoots per explant).…”
Section: Discussionsupporting
confidence: 61%
“…The shoot proliferation rate was significantly affected by addition of Gln, ADS and CH. The simulative role of ADS in shoot multiplication has been emphasized from time to time in various plants (Husain and Anis, 2004;Dhar and Upreti, 1999;Husain et al, 2008). In our study, we found 50 mg/L of ADS as highly effective for enhancing the shoot multiplication rate (4.88 shoots per explant).…”
Section: Discussionsupporting
confidence: 61%
“…In their study, reduced BA concentration (0.5 mg L -1 ) was found to be effective for shoot proliferation. The simulative role of Ads in shoot multiplication has been emphasized from time to time in various plants [26,27]. Adenine sulphate, supplied in combination with BA and IAA, enhanced the shoot multiplication by many folds during the present investigation.…”
Section: Resultsmentioning
confidence: 50%
“…3). A similar two-step rooting procedure has been used successfully for different species (Martin, 2003;Feyissa et al, 2005;Siddique and Anis, 2007;Husain et al, 2008;Conde et al, 2008). IBA at high concentration is known to suppress root elongation (Korach et al, 2002).…”
Section: Resultsmentioning
confidence: 99%